THE LELONG THÉVENET COLLECTION AND ITS FINAL DESTINATION: RECOVERY OF TYPE AND REFERRED MATERIALS OF CINGULATES DESCRIBED BY AMEGHINO - Laura Edith Cruz; Juan Carlos Fernicola (Publicación Electrónica de la Asociación Paleontológica Argentina, 2025)
At the end of the 19th century, Ameghino studied the fossils of the “conglomerado osífero” (Late Miocene, Paraná, Entre Ríos, Argentina), erecting at least 13 new species of cingulates. Some of the type specimens of these species have been considered lost, relying only on the descriptions of Ameghino and some figures of the type or referred materials of his 1889 atlas. The specimens described by Ameghino belonged to private (e.g., Lelong Thévenet, Ameghino) and public collections (e.g., those of Professor Scalabrini). This work aims to record the type specimens and referred materials of Cingulata within the Lelong Thévenet Collection and deposited in the collections housed at the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”. The Lelong Thévenet Collection was acquired by this institution in 1886, but the specimens were formally included, at different times, in the Colección Nacional de Paleovertebrados. An exhaustive search of the cingulate specimens referred to said collections was carried out, which resulted in the identification of several of them in Ameghino’s 1889 atlas. We found materials collected by Lelong Thévenet and Ameghino in the Colección Nacional de Paleovertebrados and Colección Nacional Ameghino, respectively. Many of these materials have been recognized as type specimens or referred materials of these armored mammals, identifying 10 original materials, of which four correspond to holotypes and six to referred materials; added to these, 17 casts were identified, six of them from holotypes and the other 11 referred by Ameghino in his atlas.